A dyadic approach to understanding the impact of breast cancer on relationships between partners during early survivorship. Issue 1 (December 2016) - Keesing, Sharon; Rosenwax, Lorna; McNamara, Beverley
Abstract Background The shared impact of breast cancer for women and their male partners is emerging as an important consideration during the experience of a breast cancer diagnosis, particularly during survivorship. This study aimed to explore the experiences of women and their partners during early survivorship and contributes a range of insights into the lives of those intimately affected by breast cancer. Methods In-depth interviews were completed with Australian women survivors of breast cancer (n = 8) and their partners (n = 8), between six months and five years following cessation of treatment. Questions included a focus on the women and their partners' daily experiences during early survivorship, including the management of ongoing symptoms, engagement in leisure and social interests, returning to work, communicating with each other, maintenance of the current relationship and other important roles and responsibilities. Thematic analysis was employed to determine key themes arising from the dyadic accounts of women and their partners' experiences during early breast cancer survivorship. Results Women and their partners experienced many changes to their previous roles, responsibilities and relationships during early breast cancer survivorship. Couples also reported a range of communication, intimacy and sexuality concerns which greatly impacted their interactions with each other, adding further demands on the relationship. Three significant themes were determined: (1) a disconnection within the relationship - this was expressed as the woman survivor of breast cancer needing to prioritise her own needs, sometimes at the expense of her partner and the relationship; (2) reformulating the relationship - this reflects the strategies used by couples to negotiate changes within the relationship; and (3) support is needed to negotiate the future of the relationship - couples emphasised the need for additional support and resources to assist them in maintaining their relationship during early survivorship. Conclusion It can be concluded that the early survivorship period represents a crucial time for both women and their partners and there are currently limited options available to meet their shared needs and preferences for support. Findings indicate that a suitable model of care underpinned by a biopsychosocial framework, access to comprehensive assessment, timely support and the provision of targeted resources are urgently needed to assist women and their partners during this critical time.